Pengaruh Motivasi Kerja dan Disiplin Kerja Islam terhadap Produktivitas Kerja Karyawan - Hamidah, Winda (IAIN Tulungagung, 2018)
Abstract: Every bank must be want every employees having optimal work productivity, because it will determined success or not the bank in the future. But the problems that emerged related work productivity employees at BPRS Amanah Ummah Leuwiliang Bogor is there is a lack of leader to Motivate the employees performance and level of Discipline the Islamic work is still low. Meanwhile, those factors is affect the work productivity employees. With that background, the writers research on the impact of Motivation Work employees and Discipline Islamic work against the Work Productivity employees (Study Cases at BPRS Amanah Ummah Leuwiliang Bogor). This study attempts to know how much Work Motivational influence and Islamic Discipline Work against employees Work Productivity at BPRS Amanah Ummah Leuwiliang Bogor. This research used a quantitative approach by spreading questionnaire to several employees BPRS Amanah Ummah Leuwiliang Bogor that as many as 40 employees. For analysis and the hypothesis use the multiple linear regression with software SPSS 23.0 for window. Based on T test results (partial regression coefficient test), that the variabel of Islamic Work Discipline have a significant positive affect on employee Work Productivity with significant value 0,00, meaning 0,00 < 0,05, thus giving the decision to reject Ho, from 40 samples analyzedÂ there is evidence that Work Productivity variable influenced significantly by variable of Islamic Work Discipline. Keywords: Work Motivation,Work Discipline and Work Productivity. Â